Of Gods and Books. Ritual and Knowledge Transmission in the Manuscript Cultures of Premodern India - De Simini, Florinda (Studies in Manuscript Cultures, 2016)
India has been the homeland of diverse manuscript traditions that do not cease to impress scholars for their imposing size and complexity. Nevertheless, many topics concerning the study of Indian manuscript cultures still remain to receive systematic examination. Of Gods and Books pays attention to one of these topics - the use of manuscripts as ritualistic tools. Literary sources deal quite extensively with rituals principally focused on manuscripts, whose worship, donation and preservation are duly prescribed. Around these activities, a specific category of ritual gift is created, which finds attestations in pre-tantric, as well as in smārta and tantric, literature, and whose practice is also variously reflected in epigraphical documents. De Simini offers a first systematic study of the textual evidence on the topic of the worship and donation of knowledge. She gives account of possible implications for the relationships between religion and power. The book is indsipensible for a deeper understanding of the cultural aspects of manuscript transmission in medieval India, and beyond.